Multiculturalism and minority rights in the Arab world - Kymlicka, Will; Pföstl, Eva (Oxford : Oxford University Press, 2014)
This title explores the obstacles to multiculturalism and minority rights in Arab states, including the history of European manipulation of minority politics.
9: Hobbesian Citizenship: How the Palestinians Became a Minority in IsraelINTRODUCTION; THE HOBBESIAN MOMENTS OF 1949-50; THE RISE OF CONSTITUTIONALISM AND NATIONALISM IN THE 1990s AND SINCE; CONCLUSION; 10: The Federalization of Iraq and the Break-up of Sudan; LONG-RUN PARALLELS; SHORT-RUN PARALLELS; 11: How Does the Arab World Perceive Multiculturalism and Treat its Minorities? The Assyro-Chaldeans of Iraq as a Case Study; INTRODUCTION: THE RENEWAL OF ARAB POLITICAL DISCOURSE; MULTICULTURALISM IS A REALITY IN THE ARAB WORLD
Print version record.
Includes index.
Includes bibliographical references and index.
eBooks on EBSCOhost
Keywords: Multiculturalism -- Arab countries; Minorities -- Legal status, laws, etc. -- Arab countries; Multiculturalisme -- États arabes; SOCIAL SCIENCE -- Discrimination & Race Relations; SOCIAL SCIENCE -- Minority Studies; Minorities -- Legal status, laws, etc; Multiculturalism; Arab countries; Arabische Staaten; Arab States; Minorities; Human rights; Multicultural society